Authentic Assignments in Translation Studies –Building a Bridge between Theory and Practice - Krenzler-Behm, Dinah (Vertimo studijos, 2017)
[full article, abstract in German; abstract in English] This article focuses on the findings of my doctoral thesis, which looks at the use of authentic assignments in translator training. The aim of my research project was to develop a robust, but at the same time flexible model that can be transferred to other contexts in Translation Studies. The research work is divided into two parts: a theoretical part and an empirical-analytic part. The main topic of the theoretical part is a chapter (chapter four) that discusses professional translating as the most important learning outcome of translator training. The focus of the empirical-analytic part is on documentary class observation divided into three different phases: preparation, implementation and evaluation. Nowadays, it is regarded appropriate to use authentic assignments in translation classes, because they provide students with practical relevance (by giving them the impression of how a professional trans-lator works). At the same time, these kinds of assignments increase the motivation of the students. Nevertheless there is a significant difference between translations done in university classes and the practice of